Anxiety Levels in Diabetes Mellitus Patients with Diabetic Foot Ulcers - Abiddin, Andi; Aldila Setiawan; Tri Cahyo Sepdianto (Health Access Journal, 2025)
Unmanaged diabetes can lead to various serious complications, one of which was the occurrence of diabetic foot ulcers. When patients experienced diabetic ulcers, it triggered anxiety. The aimed of this study was to determine the anxiety levels of diabetic patients with diabetic foot ulcers. The design of this study used a descriptive quantitative design with a population of 30 inpatients in the Wijaya Kusuma ward at Dr. Soedono Hospital, Madiun. The sampling used in this study was total sampling, and the method used to measure anxiety in this study was the “Hamilton Anxiety Rating Scale” (HARS), conducted from April 29 to May 4, 2024. The results found that more than half of the patients were female, and patients with anxiety levels were entirely in the severe anxiety category, with a small portion of patients aged 51-70 years experiencing severe anxiety. The study results showed that there was mild to severe anxiety in diabetic patients with diabetic foot ulcers, which was related to factors such as age, wound severity, and patient age. With this research, it was expected that healthcare professionals, especially doctors, nurses, and also the patients' families, could provide support and motivation to the patients to prevent excessive anxiety